Methodological Challenges in Living Qur’an Studies from Academic Publication in Indonesian Islamic University - Wahidah, Fatira; Amir, Abdul Muiz; Fansuri, Fuad (Institut Agama Islam Negeri Kendari, 2024)
The growing interest in Living Qur'an Studies (LQS) among scholars in Indonesia highlights its potential as a dynamic approach in Qur'anic studies. LQS emphasizes the interaction between Qur'anic teachings and lived experiences, integrating sociology, anthropology, philosophy, history, literature, and interpretation studies. Despite its promise, applying LQS consistently in academic research remains challenging. This study evaluates the quality and implementation of LQS in publications from Islamic Religious Higher Education Institutions (PTKIN) in the Sulawesi region. Through constructivist analysis, which explores how knowledge is actively shaped within academic discourse, this research assesses trends, methodologies, and challenges affecting the sustainability of LQS research. The findings highlight three key outcomes: (1) a growing trend of LQS adoption across four PTKIN institutions, (2) inconsistencies in methodological application, and (3) structural and conceptual challenges hindering the continuity of LQS. This study offers practical recommendations to improve the quality of LQS research, encouraging better methodological alignment and broader impact. By addressing these challenges, the research aims to advance LQS as a relevant field that bridges Qur'anic studies with contemporary societal contexts.